Analisis Strategi Pemasaran Bank Syari'ah Berbasis Digital FINTECH terhadap Pelayanan Nasabah Bank Muamalat KCP Metro - Tri Imelda; Nurul Mahmudah; Liberty Liberty (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2021)
Digital fintech service is a financial service innovation that uses or utilizes digital technology. Bank Muamalat KCP Metro as one of the banks that already provides digital fintech-based services, namely virtual account services, cash management system, internet banking, m-banking (M-DIN), and ATMs. The need for implementing a marketing strategy that builds customer satisfaction and trust in the service. This study aims to determine the Marketing Strategy of Bank Muamalat KCP Metro Based on Digital Fintech for Customer Service. This type of research is field research at Bank Muamalat KCP Metro. This research is descriptive qualitative. Data collection was carried out using interviews and documentation. The data sources used were primary sources through interviews with sub-branch managers, customer service, and customers of Bank Muamalat KCP Metro, while secondary sources were obtained from documentation or literature study to complement the primary data. Based on the research that has been done, it is known that Bank Muamalat KCP Metro has used several shari'ah marketing indicators, where the bank implements several components and the 7P marketing mix. The most dominant marketing strategy as a bank's existence is Promotion. Value marketing is created because of the brand, service, and process. Bank Muamalat KCP Metro is also inseparable from the three main principles of syari'ah marketing, namely devotion, simplicity and virtue. This principle is most dominantly applied by the marketing of Bank Muamalat KCP Metro, namely the Principle of Ketaqwaan. Bank Muamalat KCP Metro also needs to evaluate or improve marketing strategies related to digital fintech services, it needs continuous introduction efforts to use the system effectively and efficiently because there are still customers who do not recognize Muamalat's digital fintech services, especially virtual accounts, cash management systems, internet banking.